Placement of carved components in traditional timber houses of Kelantan and Terengganu = Penempatan komponen berukir dalam rumah kayu tradisional di Kelantan dan Terengganu - Kamaruddin, Zumahiran; Said, Ismail (Institut Alam dan Tamadun Melayu (ATMA), Universiti Kebangsaan Malaysia, 2010)
Woodcarving is considered an integral component of the vernacular Malay houses of Kelantan and Terengganu which are located in the east coast of Peninsular Malaysia. Carved components with various features were fabricated according to its placement and configuration in the interior as well as exterior setting of the houses. This paper presents an analytical study of the visual forms and placement of carved components in the timber houses of Kelantan and Terengganu which reflects its significant attributes and uses. An analytical study on ten houses in Kelantan and five houses in Terengganu was conducted by visual descriptive and interpretative analyses on 15 sets of reports and carving, measured drawings of the houses which were obtained from the Centre for the Study of Built Environment in the Malay World (KALAM) at the Department of Architecture in the Universiti Teknologi Malaysia (UTM). The method of analysis was triangulated and validated with interpretations from the prominent woodcarvers on art and crafts of woodcarving, and supported by literature of Malay woodcarving, The analysis revealed that several types of carved components with distinctive features including wall, door and window ventilation panels, roof and gate panels, railings and stringers were fitted in harmonious relationship with the architectural components within the house fabrics. The placement of these components with the specific carving motifs, shapes, sizes and layouts in the houses reflects certain orders and regional identity of the Kelantan and Terengganu traditional houses.